Inapparent Strengthening Effect of Twin Interface in Cu/Pd Multilayered Films with a Large Lattice Mismatch - Weng, Shayuan (Nanomaterials (Basel), 2019)
It has been found that there are two kinds of interfaces in a Cu/Pd multilayered film, namely, cube-on-cube and twin. However, the effects of the interfacial structure and modulation period on the mechanical properties of a Cu/Pd multilayered film remain unclear. In this work, molecular dynamics simulations of Cu/Pd multilayered film with different interfaces and modulation periods under in-plane tension are performed to investigate the effects of the interfacial structure and modulation period. The interface misfit dislocation net exhibits a periodic triangular distribution, while the residual internal stress can be released through the bending of dislocation lines. With the increase of the modulation period, the maximum stress shows an upward trend, while the flow stress declines. It was found that the maximum stress and flow stress of the sample with a cube-on-cube interface is higher than that of the sample with a twin interface, which is different from the traditional cognition. This unusual phenomenon is mainly attributed to the discontinuity and unevenness of the twin boundaries caused by the extremely severe lattice mismatch.